The Use of Jigsaw Technique to Improve Reading Comprehension of The Eighth Grade Students of SMP Negeri 12 Palu - Dinah Aprilia; Darmawan, Darmawan; Anjar Kusuma Dewi; Nur Sehang Thamrin (Universitas Cokroaminoto Palopo, 2024)
This research aims to find out the use of Jigsaw Technique to Teach Reading Comprehension of the Eight-Grade students of SMP Negeri 12 Palu. This research used a quasi experimental design consisting of experimental and control classes. The sample of this research was two classes of eight-grade students, with the amount 51 students of VIII A and VIII B. This research used a total sampling technique. In the process of collecting the data, the researcher used an instrument which contains of multiple choice and essay test. The result of the data analysis shows that the mean score of the experimental class significantly increased from 57.78 to 77.78, while the mean score of the control class increased from 60.36 to 69.52. The researcher found that the t-counted was higher than the t-table (4.65>1.678). It means that the hypothesis was accepted. In conclusion, the use of Jigsaw Technique can be applied by teachers in teaching and learning process as one of effective technique to improve Student’s reading comprehension.